Comparative Study of the Concept of Prophethood in the Holy Quran and the Deuterocanonical Bible - Kustiadi, Umar; Sani, Azwar; Wildan, Faiz (Jurnal Studi Agama, 2024)
Abstract The concept of prophethood is a complex topic to discuss, especially in terms of the role that prophets play and the messages that they bring from God. The Quran and the Deuterocanonical books offer different perspectives on this concept, with similarities and differences in their understanding of the role of prophets, their responsibilities, and the messages they convey. This qualitative-descriptive study examines the concept of prophethood in the Quran and Deuterocanonical books, focusing on the similarities and differences between the two. The study uses library research as a method to collect and analyze data from literature. The findings of the study indicate that both the Quran and Deuterocanonical books emphasize the importance of prophethood and the messages that prophets bring from God. However, there are differences in how the two texts understand the status and name of the prophet, as well as their role and tasks. The study concludes that a comparative approach to understanding the concept of prophethood can lead to a deeper and more nuanced appreciation of this important aspect of religious belief. It also emphasizes the importance of dialogue and mutual respect between different religious traditions